A construção da hegemonia burguesa na educação técnica de nível médio da ETEC: os limites da educação para a cidadania e a perspectiva da educação emancipadora - Silva, Daniel Bruno da (2018)
Historically in Brazil, professional education has been almost always dissociated from a critical and effectively citizen formation, evidencing that the objective of the ruling class has been the formation of subaltern classes solely as labor market, while the formation for the elite was focused on leadership positions. This difference in the education of the different social classes makes clear a real inequality of opportunities that the abstract concept of citizenship supposes ideologically to be universal. Changes generated by the process of economic development seem to frequently change social, cultural, legal and political dynamics, however not transforming the structural bases of bourgeois society nor emancipating individuals beyond mere formal liberties, essentially limited to interests of accumulation of capital by the class owning the means of production. Considering that this situation, despite counter-hegemonic efforts, is still persistent today, this work proposes an ontological research on education, on its objective expressions in Brazilian society and a critical reflection on the foundations of the concept of citizenship that was declared as the objective of Brazilian education since the 1980s. Accordingly, this work evaluates the limits of education in the construction of an emancipated society and aims to recognize the possibilities of an emancipatory educational activity in the historical process thought the ontology of social being, particularly in the professional education of middle level technicians. We intend to identify the relationship between the professional education of the technicians trained by the Paula Souza Center and the demands of the current mode of production. The analysis will be delimited on the adaptations of the technical courses to the current hegemonic production model, nevertheless considering historical antecedents as evidences of a continuity, hidden by the discourse of innovation and adaptation to the world of work. The data of the bibliographical and documentary sources will be analyzed and confronted from the theoretical reference of dialectical historical materialism, with the purpose of identifying and reflecting social processes, interests and conceptions that underlie the current public policies of professional education and then recognize the limits, possibilities and challenges for education to contribute to an ontological leap of the social being beyond the limits of capitalism